Web-based Application for Savings and Payment Management using CodeIgniter case study Elementary School - Mutrofin, Siti; Widodo, Arif; Kurniawan, Eddy (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Schools often face problems in manually recording student contributions and savings: ineffectiveness, inefficiency, and inaccuracies in recording, calculating, or the three data are needed again. In this study, we offer Savings Management Information Systems (SiMantab), which aim to solve these problems. In order to realize the research objectives, we proposed to apply CodeIgniter to develop SiMantab for recording student data, student guardians, information on savings, reports on student transactions, and payments. The outcomes of this research are: 1) SiMantab can generate daily savings reports for each student and provide reports for student guardians'; 2) SiMantab allows student guardians to monitor payment activities such as tuition fees in auto debit savings; 3) SiMantab is able to convey information bills statement on the student guardian's menu; and 4) The school obtain information on students' payments record based on the student data such as gender and class displayed on the supervisor's main menu.